Missionary principles and practice - Allen, Roland, 1869-1947.; Stanley, Brian, 1953- (Cambridge, U.K. : Lutterworth Press, 2006)
First published in 1913, Missionary Principles is a classic textbook by genre, but in its controversial evaluation of the Church's missionary theories, it is by no means wholly traditional. At the centre of this discursive study, Allen asserts the distinction which needs to be made in missionary aims between the extension of the Church and the preaching of Jesus Christ. The book is divided into four major chapters, entitled: The Impulse, The Hope, The Means and The Reaction. The impulse, hope and means of missionary work can all be embodied by Jesus Christ, who is viewed as the source, the end.
Front cover; Title Page; Foreword by Brian Stanley; Contents; Chapter 1: The Impulse; Chapter 2: The Hope; Chapter 3: The Means; Chapter 4: The Reaction; Back cover.
Originally published: London : Robert Scott, 1913.
Keywords: Missions -- Theory; Missions; RELIGION -- Christian Ministry -- Missions; Missions; Missions -- Theory; RELIGION / Christian Ministry / Missions; Electronic books